Paraneoplastic lipase and amylase production in a patient with small-cell lung cancer: case report - Casadei Gardini, Andrea (BMC Cancer, 2016)
BACKGROUND: Small-cell lung cancer (SCLC) is known to express antigens of both the neural crest and epithelium, and to secrete polypeptide hormones and enzymes. Anecdotal reports correlate lung cancer with marked hyperamylasemia, and a review of the literature reveals only one case of metastatic SCLC linked to high paraneoplastic lipase production. CASE PRESENTATION: We present the case of a patient with metastatic SCLC who showed both lipase and pancreatic isoamylase elevation in the absence of acute pancreatitis. Chemotherapy resulted in a rapid reduction in serum lipase and in pancreatic isoamylase which was correlated with the radiological response of the tumor to therapy. Lipase and pancreatic isoamylase expression in tumor cells from the lung biopsy was confirmed by immunohistochemical staining. CONCLUSIONS: This is a very rare case of paraneoplastic syndrome linked to metastatic SCLC. The enzymes secreted could be used as markers of response to treatment until clonal selection mechanisms and intratumor heterogeneity induce changes in biochemical characteristics and consequently in tumor behavior.